Vegetativnoe obespecenie kardiorespiratornoj sistemy sportsmenov razlicnych specializacij - Romancuk, A. P.; Ovcarek, A. M.; Braslavskij, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
In the work the differences of the vegetative maintenance of cardiorespiration system at various orientation of a training process are shown with the help of the spiroarteriocardiorythmography on the example of the analysis of the results of the inspection of the qualified athletes engaged in running and volleyball. The marked features are the most expressed for the vegetative maintenance of cardiac rhythm and systolic arterial pressure.